Effects of Adding BreatheMAX-Assisted Deep Breathing to Home-Based Spot Marching on Maximal Voluntary Ventilation and Peak Expiratory Flow in Young Adults with Overweight or Obesity: A Randomized Controlled Trial - Sujittra Kluayhomthong; Nontanat Sathaporn; Parkpoom Pipatbanjong; Umaporn Panpang; Kanyanat Kanka; Noppasorn Promman; Phanpan Inthajark; Sasit Sutawong; Pakhin Thamwiwat; Suntichai Prachumkhong; Vitsarut Buttagat (International Journal of Environmental Research and Public Health, 2026)
Background: Overweight and obesity adversely affect respiratory mechanics and ventilatory capacity. This study evaluated the incremental effects of combined Spot Marching Exercise and BreatheMAX-assisted deep breathing (CSMEB) versus Spot Marching Exercise alone (SME) on pulmonary function in young adults with overweight/obesity. Methods: Thirty-eight participants (aged 18–25 years, BMI 25.0–39.9 kg/m2) were randomized into SME (n = 19) or CSMEB (n = 19) groups, with 36 completing the study (18 per group) after two withdrew before treatment. Both performed 30 min of SME 5 days/week for 8 weeks; CSMEB additionally performed daily device-assisted deep breathing (10 sets of 10 breaths). The primary outcome was maximal voluntary ventilation (MVV). Secondary outcomes included spirometry and body composition parameters. Results: At Week 8, CSMEB achieved significantly greater improvements in MVV compared to SME (adjusted mean difference = 6.31 L/min; 95% CI: 0.08–12.55; p = 0.047). Peak expiratory flow rate (PEFR) also significantly favored CSMEB (adjusted mean difference = 0.71 L/s; 95% CI: 0.02–1.39; p = 0.044). No significant between-group differences were found for FVC, FEV1, FEV1/FVC, muscle mass, or body fat percentage (p > 0.05). No adverse events occurred. Conclusions: Adding BreatheMAX-assisted deep breathing to a home-based SME program yields targeted enhancements in MVV and PEFR in young adults with overweight or obesity.